The Use of STEM Integrated Project-Based Learning Media Assisted by TikTok Application to Improve Students’ Creative Thinking Skills - Cut Hayati; Muhammad Syukri; Agus Wahyuni; Tiara Shandi; Susilawati, Susilawati; Ngadimin, Ngadimin (Jurnal Pendidikan Fisika, 2025)
Creativity is recognized as a central competency for twenty-first-century learners. Yet, physics classrooms often remain dominated by formulaic instruction that limits opportunities for students to exercise higher-order thinking. This study addresses the urgent need to foster creative thinking in physics, particularly in abstract topics such as projectile motion, by integrating TikTok media into a Project-Based Learning integrated STEM framework. The research aimed to investigate the effect of this integration on students’ creative thinking skills, measured across four indicators: fluency, originality, flexibility, and elaboration. Employing a quasi-experimental design with a nonequivalent control group, the study involved 67 Grade XI students from a senior high school in Makassar, Indonesia. The experimental group (n = 35) received instruction using Project-Based Learning–STEM with TikTok, while the control group (n = 32) learned through Project-Based Learning –STEM without TikTok. Data were collected using an essay-based test validated by experts and analyzed using normalized gain (N-gain) and an independent samples t-test. Results showed that the experimental class achieved significantly higher posttest scores, with N-gain in the high category (0.74) compared to the medium category in the control group (0.52). The greatest improvements were observed in elaboration and originality, reflecting the platform’s affordances for encouraging detailed explanations and unique representations of physics concepts. The findings confirm that integrating culturally relevant digital platforms within structured pedagogical designs enhances creativity beyond affective engagement. This study contributes to physics education by providing empirical evidence that TikTok, when aligned with PjBL–STEM, can bridge everyday digital practices with disciplinary learning to foster creativity, offering a novel and practical pathway for innovation in science education.